Training energy systems - Ogita, F. (World book of swimming: From science to performance, 2012)
The primary purpose for training energy systems is to improve swimming performance by enhancing the ability to produce energy from anaerobic and aerobic processes. Endurance training which is performed at sub-maximal intensities, i.e. from around lactate threshold to VO2max, enhances lactate removal, and improves cardio-respiratory functions for oxygen delivcry, as well as muscular oxidative capacity for oxygen utilization. Anaerobic training which produces a significant amount of lactic acid induces an increase in the enzymatic activity of the glycolytic system as well as the muscle's buffering capacity. Finally, sprint training lasting less than 10 seconds enhances the ATP-PCr system and glycolytic system, but could decrease some resting metabolites stores, such as ATP and PCr. Since the effect of training on each energy system depends strongly on training intensities, it is of major importance to understand why training intensities have to be carefully set to optimally stress and maximally potentiate each energy system.